Anisotropic thermal conductivity of 4H and 6H silicon carbide measured using time-domain thermoreflectance. (December 2017) - Qian, Xin; Jiang, Puqing; Yang, Ronggui
Abstract: Silicon carbide (SiC) is a wide bandgap (WBG) semiconductor with promising applications in high-power and high-frequency electronics. Among its many useful properties, the high thermal conductivity is crucial. In this letter, the anisotropic thermal conductivity of three SiC samples, n-type 4H-SiC (N-doped 1 × 10 19  cm −3 ), unintentionally doped (UID) semi-insulating (SI) 4H-SiC, and SI 6H-SiC (V-doped 1 × 10 17  cm −3 ), is measured using femtosecond laser based time-domain thermoreflectance (TDTR) over a temperature range from 250 K to 450 K. We simultaneously measure the thermal conductivity parallel to ( k r ) and across the hexagonal plane ( k z ) for SiC by choosing the appropriate laser spot radius and the modulation frequency for the TDTR measurements. For both k r and k z, the following decreasing order of thermal conductivity value is observed: SI 4H-SiC > n-type 4H-SiC > SI 6H-SiC. This work serves as an important benchmark for understanding thermal transport in WBG semiconductors. Graphical abstract: Highlights: First systematic measurement of the anisotropic thermal conductivity of 4H and 6H SiC. The thermal conductivity of SiC samples are observed to be: k(SI 4H) > k(n-type 4H)> k(SI 6H). Important benchmark for understanding thermal transport in WBG semiconductors.